2015
DOI: 10.1080/03004279.2015.1089920
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on the standards agenda: exploring the agenda's impact on primary teachers' professional identities

Abstract: This study aimed to investigate teachers' perspectives on the practical implementation of the standards agenda and its impact on their professional identities. Q-methodology was used alongside semi-structured interviews with UK primary school teachers. The study explored the views of 25 teachers in 6 schools, selected through purposive sampling to give a range of individual and institutional demographics. Teachers in this research commented on the impact the standards agenda has had on parental and societal ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 33 publications
2
31
0
1
Order By: Relevance
“…However, research on the interrelation between school reform implementation strategies and the stress experienced by those responsible for it is surprisingly scarce. A few studies have focused primarily on teachers and principals involved in standard-based reforms characterised by high accountability (see Brown and Manktelow 2016;Lainas 2010;Lasky 2005;Valli and Buese 2007). Accordingly, little is known about how reform implementation strategies, in national non-standardised reforms, contribute to both meaningful learning and burdening for those carrying out the reform work.…”
Section: Introductionmentioning
confidence: 99%
“…However, research on the interrelation between school reform implementation strategies and the stress experienced by those responsible for it is surprisingly scarce. A few studies have focused primarily on teachers and principals involved in standard-based reforms characterised by high accountability (see Brown and Manktelow 2016;Lainas 2010;Lasky 2005;Valli and Buese 2007). Accordingly, little is known about how reform implementation strategies, in national non-standardised reforms, contribute to both meaningful learning and burdening for those carrying out the reform work.…”
Section: Introductionmentioning
confidence: 99%
“…MCAS labels students through a system based on standardized testing and data points as exceeding expectations, meeting expectations, partially meeting expectations, or not meeting expectation decisions (Massachusetts Department of Elementary and Secondary Education, 2018). As a consequence of the labeling and comparison of students, educators have identified a change in parental views toward teachers, increases in the questioning of teacher judgment, and the narrowing of the curriculum and instruction, resulting in a conflict between teachers and society as to the purpose of education (Au, 2011;Brown & Manktelow, 2016;McNess et al, 2003).…”
Section: Context and Backgroundmentioning
confidence: 99%
“…Many schools across the United States have implemented the CCSS as a guideline to have all students ready for entry-level careers, college coursework, or workforce training programs (CCSS Initiative, 2016). These new standards assist teachers in measuring student progress with a reliance on common assessments such as standardized testing that move away from teacher judgment of student progress (Brown & Manktelow, 2016). Literature has shown that the tendency to expect academic conformity shifts pedagogy to increase testing results through testing preparation (Brown & Manktelow, 2016).…”
Section: Research Problemmentioning
confidence: 99%
See 2 more Smart Citations